The effect of an isometric hip muscle strength training protocol on valgus angle during a drop vertical jump in competitive female volleyball players - Jackson, K. M.; Beach, T. A. C.; Andrews, D. M. (International Journal of Kinesiology & Sports Science, 2017)
Hip muscle weakness is associated with higher peak knee valgus angles (VA) during drop vertical jumps (DVJ) and linked to ACL injury risk. Objective: To determine if isometric strengthening (IST) of the hip extensor, abductor, and external rotator muscle groups would reduce VA exhibited during a DVJ. Methodology: Fourteen female volleyball players (7 training (TG), 7 control (CG), VA=9° during DVJ) participated. Pre- and post-test gluteal, quadriceps and hamstring strength were measured with a digital force gauge. Three-dimensional kinematics were collected during 15 DVJ trials. TG participated in a 6-week IST program that targeted the hip extensor, abductor, and external rotator muscle groups. Two-way mixed ANOVAs compared mean differences of VA and strength. Single-participant analyses examined if athlete-specific adaptations went undetected in the analyses of aggregated data. Results: TG hip extension, abduction, and knee flexion strength increased, respectively, by 20.5%, 27.5% and 23.5% (P<0.05). No group-level changes in VA were detected. Unilateral VA decreased for 5 TG participants, and bilateral VA decreased in 2 TG participants. Conclusions: IST increased isometric hip muscle strength, but its effect on VA is inconclusive based on group-level analyses. Using single-participant designs, future studies should assess IST and/or dynamic resistance/neuromuscular training in a larger sample to determine its effect on ACL injury risk factors.